FORMATION OF ANTI-CORRUPTION BEHAVIOR AMONG GRADUATES OF DISTANCE LEARNING FACULTIES - Oybek Kamalov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article emphasizes the importance of the code of professional culture and service discipline of employees of internal affairs bodies in the early prevention of cases of corruption.